(untitled) (University of Khartoum Engineering Journal, 2022)
The objective of this work is to provide analytical solution of the conservation equations governing the desiccant wheel. The conservation equations describing the moisture exchange between wheel matrix and airflows are complicated partial differential equations (PDEs). This complication is brought about by space and time variations of moisture content. In this work conservation equations of moisture in the matrix and in airflow were solved using the method of successive transformation of variables. In this process the complicated PDEs were reduced to an ordinary Bessel differential Eq. of the type xf   f   xf  0 ; which has a general solution of ( ) ( ) ( ) 1 0 2 0 f x C I x C K x . The analytical solution has facilitated exact determination of moisture distribution in the matrix and in supply and regeneration airflows. It can also be used to accurately predict the wheel performance parameters such as moisture removal and latent effectiveness. In addition provision of analytical solution to the problem has made significant contribution to the understanding of the complicated desiccant wheel operation principles.